Analyzing the System Performance for Compression Encrypted Images Using Hybrid DWT-DCT-DST Compression Algorithm - صالح, السمؤل; علي, صادق; سرحان, خلود (Latakia University Journal -Engineering Sciences Series, 2020)
Recently, the field of multimedia and network technologies has developed greatly. With this development, the information security has become the most important part of multimedia-based system when the data is transmitted over the network. If encryption is not applied, the information may be stolen. on the other hand, Image compression is also essential where images need to be stored, transmitted or viewed quickly and efficiently. Therefore, there is a need for a system that applies encryption before the image compression. In this research, we propose an encryption method that is operated with Arnold transform and image compression algorithm using Discrete Wavelet Transform (DWT), Discrete Cosine Transform (DCT) and Discrete Sine Transform (DST) that can be used efficiently to compress the encrypted image. To achieve our goal, we used several normal and medical images. We conducted a performance test for (6) different types of mother wavelets, in order to select the optimal mother wavelet that achieves the best compression ratio and maintains best quality of the reconstructed image. We evaluated the results using Peak Signal to Noise Ratio (PSNR), Compression Ratio (CR) and Root Mean Square Error (RMSE) parameters. In order to have a visual perception, subjective evaluation of the images have been conducted. The simulation was performed using MATLAB. The results showed that (bior3.9) achieved the best quality of the reconstruction image. The proposed algorithm achieved good results for compression and quality of medical images.